Pemilihan Lokasi Budidaya Rumput Laut Menggunakan Metode Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW) - Sri Rahayu; Hamdani Hamdani; Ramadiani Ramadiani (JISKA (Jurnal Informatika Sunan Kalijaga), 2022)
One of the professions in the marine sector that is mostly occupied by people living in coastal areas is seaweed cultivation. Seaweed is one of the marine product commodities with great potential to be developed in Indonesia because it has high economic value. One of the areas that are included as producers of Eucheuma Cottonii seaweed is Nunukan Island, which is located in Nunukan Regency, North Kalimantan Province. The main factor that determines success in seaweed cultivation activities is the selection of land locations. Errors in site selection can lead to crop failure and low quality of the seaweed produced. The purpose of this study is to create a decision support system to facilitate and assist the community in selecting the best location for seaweed cultivation quickly and precisely according to the criteria using the Analytical Hierarchy Process (AHP) method to calculate the criteria weights and the Simple Additive Weighting (SAW) method for performing alternative ratings. The criteria used were 7, namely depth, pH, current speed, brightness, temperature, salinity, and dissolved oxygen, while alternative data were 11 points of seaweed cultivation locations on Nunukan Island. Based on the results of the implementation of the two methods, recommendations for two locations for seaweed cultivation are Sei Banjar I and Sei Banjar II with the same preference value of 0.937 which is the highest value compared to other alternatives.